Phytochemicals and The Ability of Plantago major Linn. Extract to Inhibit The growth of Aeromonas hydrophila - Dewi, Annisa Farhana; Prajitno, Arief; Yuniarti, Ating (The Journal of Experimental Life Science, 2019)
Aeromonas hydrophila is a type of gram-negative bacteria that can harm humans and major animals that have poikilotherm properties such as fish and shrimp. These bacteria can cause haemorrhages in fish until death and causing fish farming production to failure. The use of medicinal plants has been trusted by people all over the world to overcome various disease problems, one of which is a disease caused by bacteria. Plantago major L. is known that able to inhibit the growth of both gram-positive and gram-negative bacteria. The purposes of this study were to identify the extracted compounds contained in Plantago major L., using FTIR and UV-VIS spectrophotometer and to evaluate antibacterial activity against A. hydrophila. The results of this study showed that crude extracts of Plantago major L. contained polar compounds such as phenols, flavonoids, saponins, and tannins. The presence of phenols and flavonoids was confirmed by the results of FTIR and UV-VIS. Furthermore, the crude extract of Plantago major L. significantly inhibited the growth of A. hydrophila (P <0.05).Keywords: Antibacterial, Co-culture, Extraction, FTIR, UV-VIS.